Early crustal processes revealed by the ejection site of the oldest martian meteorite - Lagain, Anthony; Bouley, S.; Zanda, B.; Miljković, Katarina; Rajšić, Andrea; Baratoux, D.; Payré, V.; Doucet, Luc; Timms, Nick; Hewins, R.; Benedix, Gretchen; Malarewic, V.; et al. (2022)
The formation and differentiation of the crust of Mars in the first tens of millions of years after its accretion can only be deciphered from incredibly limited records. The martian breccia NWA 7034 and its paired stones is one of them. This meteorite contains the oldest martian igneous material ever dated: ~4.5 Ga old. However, its source and geological context have so far remained unknown. Here, we show that the meteorite was ejected 5–10 Ma ago from the north-east of the Terra Cimmeria—Sirenum province, in the southern hemisphere of Mars. More specifically, the breccia belongs to the ejecta deposits of the Khujirt crater formed 1.5 Ga ago, and it was ejected as a result of the formation of the Karratha crater 5–10 Ma ago. Our findings demonstrate that the Terra Cimmeria—Sirenum province is a relic of the differentiated primordial martian crust, formed shortly after the accretion of the planet, and that it constitutes a unique record of early crustal processes. This province is an ideal landing site for future missions aiming to unravel the first tens of millions of years of the history of Mars and, by extension, of all terrestrial planets, including the Earth.